Effect of soil and foliar applied nutrients on growth, yield and nutrient content of Indian mustard (Brassica juncea L.) - THAKUR, JYOTI; SHEORAN, HARDEEP SINGH; SHEORAN, SEEMA; DEEPIKA; PARIHAR, M.D.; BALA, MANJU (Journal of Soil and Water Conservation, 2026)
A field experiment was conducted during rabi season of 2024-25 at Soil Research Farm, CCS Haryana Agricultural University, Hisar, to study the effect of soil and foliar application of nutrients on growth, yield and nutrient content of Indian mustard. The experiment was laid out in Randomized Block Design with 10 treatments in three replications. The results of the study revealed that application of RDF along with NPK (19:19:19) and seaweed extract at flowering and siliqua formation stages (T10) significantly increased the growth parameters, yield and yield attributes along with an improved harvest index of the mustard over control. The seed yield, stover yield and harvest index of mustard in T10 increased significantly to 2095 and 5754 kg ha-1 and 26.6%, respectively over control. The highest NPK content in seed (2.42, 0.51, 1.01%) and stover (0.77, 0.34, 2.82%) was also observed in T10 where RDF + NPK (19:19:19) and seaweed extract at flowering and siliqua formation stages was applied which was statistically at par with T9, i.e. NPK content of 2.32, 0.45, 0.94% in seed and 0.72, 0.32, 2.79% in stover, respectively. Application of RDF + 0.2% B + 1% K2SO4 at flowering and siliqua formation (T8) showed highest concentration of sulphur (0.44% in seed and 0.27% in stover) and boron (26.99% in seed and 24.61% in stover) in both seed as well as stover in mustard over control. Overall, it can be concluded that combined soil and foliar nutrient treatments could enhanced the absorption of nutrients, especially during critical growth stages and thereby sustaining the mustard yield.